Design, synthesis and biological evaluation of novel triazoloquinazolinone and imidazoquinazolinone derivatives as allosteric inhibitors of SHP2 phosphatase - Wenjun Ye; Ye Liu; Qian Ren; Tianhui Liao; Yumei Chen; Dongmei Chen; Sisi Wang; Lihong Yao; Yihe Jia; Chunshen Zhao; Zhixu Zhou (Taylor & Francis Group, 2022)
A series of novel triazoloquinolinone and imidazoquinazolinone derivatives were designed and synthesised, and their biological activities against SHP2 protein and melanoma A357 cell line were evaluated in vitro. The results show that some target compounds have moderate to excellent inhibitory activity on SHP2 protein and melanoma A357 cell line. Structure-activity relationships (SARs) showed that both imidazoquinazolinone and triazoloquinazolinone derivatives have good SHP2 protein kinase and melanoma cell line A357 inhibitory activity. The results of molecular docking also showed that the cores of imidazoquinazolinone and triazoloquinazolinone have a certain affinity for SHP2 protein at the same time. Compared with SHP244, the target compounds have quite good liver microsomal stability and has more drug potential. The most promising compound B1 has a strong inhibitory effect on the melanoma cell line A357 at 100 µM (76.15% inhibition).